The NF-κB Inhibitor Curcumin Blocks Sepsis-Induced Muscle Proteolysis - Vitaliy Poylin; Moin U. Fareed; Patrick O'Neal; Nima Alamdari; Natasha Reilly; Michael Menconi; Per-Olof Hasselgren (Mediators of Inflammation)
We tested the hypothesis that treatment of rats with curcumin prevents sepsis-induced muscle protein degradation. In addition, we determined the influence of curcumin on different proteolytic pathways that are activated in septic muscle (i.e., ubiquitin-proteasome-, calpain-, and cathepsin L-dependent proteolysis) and examined the role of NF-κB and p38/MAP kinase inactivation in curcumin-induced inhibition of muscle protein breakdown. Rats were made septic by cecal ligation and puncture or were sham-operated. Groups of rats were treated with three intraperitoneal doses (600 mg/kg) of curcumin or corresponding volumes of solvent. Protein breakdown rates were measured as release of tyrosine from incubated extensor digitorum longus muscles. Treatment with curcumin prevented sepsis-induced increase in muscle protein breakdown. Surprisingly, the upregulated expression of the ubiquitin ligases atrogin-1 and MuRF1 was not influenced by curcumin. When muscles from septic rats were treated with curcumin in vitro, proteasome-, calpain-, and cathepsin L-dependent protein breakdown rates were reduced, and nuclear NF-κB/p65 expression and activity as well as levels of phosphorylated (activated) p38 were decreased. Results suggest that sepsis-induced muscle proteolysis can be blocked by curcumin and that this effect may, at least in part, be caused by inhibited NF-κB and p38 activities. The results also suggest that there is not an absolute correlation between changes in muscle protein breakdown rates and changes in atrogin-1 and MuRF1 expression during treatment of muscle wasting.